2015
DOI: 10.1590/s1517-838246320140402
|View full text |Cite
|
Sign up to set email alerts
|

Interspecific transmission of small ruminant lentiviruses from goats to sheep

Abstract: This study was conducted in order to evaluate the transmission of caprine lentivirus to sheep using different experimental groups. The first one (colostrum group) was formed by nine lambs receiving colostrum from goats positive for small ruminant lentiviruses (SRLV). The second group (milk group) was established by nine lambs that received milk of these goats. Third was a control group, consisting of lambs that suckled colostrum and milk of negative mothers. Another experimental group (contact group) was forme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
30
1
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(38 citation statements)
references
References 31 publications
2
30
1
5
Order By: Relevance
“…Different clinical manifestations are known, the main ones being arthritis, pneumonia, encephalitis and mastitis, besides progressive weight loss (Pasick, 1998;Souza et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Different clinical manifestations are known, the main ones being arthritis, pneumonia, encephalitis and mastitis, besides progressive weight loss (Pasick, 1998;Souza et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…In this sense, the transmission of caprine lentivirus to sheep has already been proved (Souza et al, 2015), but it is not yet clear whether animals infected with heterologous strains can transmit the infection. Thus, the objective of the present experiment was to detect the presence of caprine lentivirus proviral DNA in the milk and semen of experimentally infected sheep.…”
Section: Introductionmentioning
confidence: 99%
“…Intrauterine transmission has not been discarded yet (ALVES, 2015). Interspecies transmission of SRLV is mainly through the contact of infected sheep and goats and by the ingestion of contaminated colostrum or milk of infected goat nannies (SOUZA et al, 2015b). In 2015, SOUZA et al (2015a demonstrated the virus in saliva, which may play an important role in the epidemiology of the disease if it is infectious.…”
Section: Palavras-chave: Perdas Produtivas; Lentivírus De Pequenos Rumentioning
confidence: 99%
“…These characteristics are limiting factors for controlling SRLV diseases, which lead to significant economic losses, mainly in dairy production. In addition, SRLV may migrate to several different tissues and fluids, hindering the detection and favoring transmission (PISONI et al, 2007), including interspecies (SOUZA et al, 2015b).…”
Section: Palavras-chave: Perdas Produtivas; Lentivírus De Pequenos Rumentioning
confidence: 99%
“…Afectan a ovinos y caprinos transmitiéndose naturalmente entre ambas especies (Narayan et al, 1980;Pepin et al, 1998;Jolly et al, 1989;Minguijon et al, 2015) y pueden producir cuatro formas clínicas clásicas: pulmonar, nerviosa, mamaria y articular. La forma pulmonar se caracteriza histopatológicamente por neumonía del tipo intersticial, notorio incremento de tamaño visceral, acompañado de disnea y caquexia; la forma nerviosa se produce en animales jóvenes, entre 2 y 3 meses presentando una encefalitis linfocítica con o sin afección medular y los animales se muestran atáxicos; en la glándula mamaria se produce una mastitis intersticial con fibrosis, reducción de la producción láctea y el endurecimiento del tejido; por último la forma articular se caracteriza por una proliferación de la membrana sinovial en capas que causa un engrosamiento artrítico con erosión de las superficies articulares, principalmente carpos, que produce rengueras crónicas, menor consumo, producción e incluso postración del animal (Narayan et al, 1980;Minguijon et al, 2015;De Souza, 2015;Zink y Jonhnson, 1994). La artritis crónica se observa principalmente en animales mayores de un año (Jones et al, 1997;Smith y Sherman, 1994;Radostits et al, 2002).…”
Section: Introductionunclassified